Impact of Patient‐Centered Discharge Tools: A Systematic Review. Issue 2 (1st February 2017) - Okrainec, Karen; Lau, Davina; Abrams, Howard B.; Hahn‐Goldberg, Shoshanna; Brahmbhatt, Ronak; Huynh, Tai; Lam, Kenneth; Bell, Chaim M.
Abstract : BACKGROUND: Patient‐centered discharge tools provide an opportunity to engage patients, enhance patient understanding, and improve capacity for self‐care and postdischarge outcomes. PURPOSE: To review studies that engaged patients in the design or delivery of discharge instruction tools and that tested their effect among hospitalized patients. DATA SOURCES: We conducted a search of 12 databases and journals from January 1994 through May 2014, and references of retrieved studies. STUDY SELECTION: English‐language studies that tested discharge tools meant to engage patients were selected. Studies that measured outcomes after 3 months or without a control group or period were excluded. DATA EXTRACTION: Two independent reviewers assessed the full‐text papers and extracted data on features of patient engagement. DATA SYNTHESIS: Thirty articles met inclusion criteria, 28 of which examined educational tools. Of these, 13 articles involved patients in content creation or tool delivery, with only 6 studies involving patients in both. While many of these studies (10 studies) demonstrated an improvement in patient comprehension, few studies found improvement in patient adherence despite their engagement. A few studies demonstrated an improvement in self‐efficacy (2 studies) and a reduction in unplanned visits (3 studies). CONCLUSIONS: Improving patient engagement through the use of media, visual aids, or by involving patients when creating or delivering a discharge tool improves comprehension. However, further studies are needed to clarify the effect on patient experience, adherence, and healthcare utilization postdischarge. Better characterization of the level of patient engagement when designing discharge tools is needed given the heterogeneity found in current studies.